2014
DOI: 10.1371/journal.pone.0095689
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D Supplementation Enhances the Fixation of Titanium Implants in Chronic Kidney Disease Mice

Abstract: Vitamin D (Vit D) deficiency is a common condition in chronic kidney disease (CKD) patients that negatively affects bone regeneration and fracture healing. Previous study has shown that timely healing of titanium implants is impaired in CKD. This study aimed to investigate the effect of Vit D supplementation on implant osseointegration in CKD mice. Uremia was induced by 5/6 nephrectomy in C57BL mice. Eight weeks after the second renal surgery, animals were given 1,25(OH)2D3 three times a week intraperitoneally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 44 publications
(50 reference statements)
3
58
0
4
Order By: Relevance
“…reported an improved titanium screw fixation in ovariectomized rats after 8 weeks of oral treatment with vitamin D, showing a significant increment of peri‐implant bone density, bone‐implant contact (1.5 times higher) and peri‐implant trabecular microarchitecture . Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD . Recently, the effect of topical application of vitamin D (10%) and melatonin (5%) solutions on the surface of immediate implants placed in dogs was evaluated.…”
Section: Factors Affecting Bone Metabolismmentioning
confidence: 64%
“…reported an improved titanium screw fixation in ovariectomized rats after 8 weeks of oral treatment with vitamin D, showing a significant increment of peri‐implant bone density, bone‐implant contact (1.5 times higher) and peri‐implant trabecular microarchitecture . Similar results were reported in mice with chronic kidney disease (CKD), suggesting that vitamin D treatment may be an effective approach for implant placement in patients with CKD . Recently, the effect of topical application of vitamin D (10%) and melatonin (5%) solutions on the surface of immediate implants placed in dogs was evaluated.…”
Section: Factors Affecting Bone Metabolismmentioning
confidence: 64%
“…The causes of early implant failure are not fully clarified and an association between vitamin D and dental implant osseointegration has not been investigated properly [8, 1316]. Some recent animal studies in rodents demonstrated a relationship between vitamin D supplementation and an increased bone to implant contact/volume after implant placement [14, 34, 35]. Mengatto et al demonstrated an impaired osseointegration in vitamin D-deficient rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…A study on mice showed that vitamin D improved osseointegration after the insertion of dental implants. Histomorphometric analysis revealed that animals which received vitamin D supplements, had higher values of bone-implant contact and bone volume around the implants compared with the controls (Liu et al 2014). In another study Zhang et al (2007) demonstrated that the reduction in VDR resulted in the development of teeth structure disturbances in experimental mice.…”
Section: Bone and Teeth Metabolismmentioning
confidence: 96%